Uji Efektifitas Insektisida Biologi terhadap Hama Penggerek Polong (Maruca testulalis Geyer.) (Lepidoptera ; Pyralidae) pada Tanaman Kacang Panjang di Lapangan - Eka Sundari Saragih; Yuswani Pangestiningsih (Universitas Sumatera Utara, 2015)
The objective of this research was to get bioinsecticides that efective againts the borer on chickpea in the field. This research was conducted at the Desa Kerapuh Kecamatan Dolok Masihul Kabupaten Serdang Bedagai, from November 2013 until Januari 2014. The research used complete block design nonfactorial with eight treatments and three replications. The treatments were control, Leaf extract of betelvine 100 g/l, leaf extract of soursop 250 g/l, Extract of Derris 50 g/l, Leaf extract of papaya 100 g/l, Bacillus thuringiensis 1ml/l, Beauveria bassiana 10 gr/l and Klorantraniliprol 1 ml/liter. The result showed that kind of bioinsecticide gave different effect to all of parameters. The best bioinsecticide to control M. testulalis was leaf extract of soursop 250 gram/liter.Key words: Maruca testulalis, chickpea, bioinsecticide